FOOD TOURISM DEVELOPMENT IN NAKHON NAYOK PROVINCE - Sinnang, Panlayamon (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2024)
Objectives: 1) To create a street food tourism route in Nakhon Nayok Province. 2) To study consumer decision-making trends in traveling to consume products in Nakhon Nayok Province. 3) To find baseline data for the street food tourism route in Nakhon Nayok Province. This research is a mixed method research combining quantitative research with a sample group of 400 people and qualitative research by interviewing 10 restaurant operators. Data was analyzed using statistics, percentages, mean, and standard deviation. Content analysis statistics were also used. The research results are as follows: 1) The street food tourism route in Nakhon Nayok Province is as follows: Restaurant 1: Legendary Fresh Fish Noodle, Restaurant 2: Pa Tuk’s Grilled Chicken, Restaurant 3: Ratree Congee, Restaurant 4: Thanakorn Nakhon Nayok BBQ, Restaurant 5: Pad Thai Champion, Restaurant 6: Rad Na Yot Pak, Restaurant 7: Pa Daeng’s Som Tum, Ban Dong, Restaurant 8: Suan Si Thong, Restaurant 9: Khrua Lung Kang, and Restaurant 10: Sukea Boran Baan Mae. 2) Consumer decision-making trends in traveling to consume products in Nakhon Nayok Province are as follows: Consumers place the most importance on products (= 4.23). Therefore, operators must place importance on products, namely food, price, and physical appearance, which are the reasons for consumers’ decisions to purchase food. Operators and relevant government and private sector agencies must place importance on pricing so that it is appropriate for the quality of the food and not unfair to consumers. Relevant agencies must also provide support and organize the area into a street food zone. 3) Baseline data for the street food tourism route in Nakhon Nayok Province.